Differences in service quality of retail banking between Auckland and Kuala Lumpur - Abdullah, Moha Asri; Abd. Manaf, Noor Hazilah; Ahsan, Kamrul; Azam, Ferdous (World Business Institute, 2015)
The consciousness of service quality has been catching the light worldwide. The aim of this paper is to identify the differences in service quality of retail banking between Auckland and Kuala Lumpur. This research surveyed a sample of 236 bank customers from both places, consisting 115 New Zealander from Auckland and 121 Malaysian from Kuala Lumpur region. The results draw the clear differences in service quality of retail banking between Auckland and Kuala Lumpur in terms of latest service technology, front office facilities, neat-appearing employees, solving a customer problem, performing service right the first time, accuracy of banking records, security, confidence and willingness to help customers, operating hours, sufficient ATM’s and branches as well as community programs and so on. Thus, the findings reveal the most obvious implications, considering banking service providers to further improve their service quality with greater efficiency and as a way to better compete in the current marketplace.